Ultrasound diagnosis of pancreatic tumors (Texas Journal of Medical Science, 2022)
In patients with solid pancreatic lesions, the differential diagnosis must be evaluated to determine whether radical surgery, pancreatic parenchyma-saving strategies, or follow-up is indicated. Contrastenhanced (endoscopic) ultrasonography and elastography facilitate the further characterization of SPLs. The majority of cases of pancreatic ductal adenocarcinoma exhibit hypoenhancement with contrastenhanced ultrasonography. Elastographically soft SPLs are benign with very few exceptions, whereas stiffer SPLs can be malignant or benign. This article reviews the current use of modern ultrasound imaging techniques, including contrast-enhanced ultrasonography and elastography, for the detection and characterization of SPLs. In particular, the unexcelled diagnostic potential of multiparametric endoscopic ultrasonography to detect and characterize small SPLs is highlighted.